Initiation and response of joint attention bids in autism spectrum disorder children depend on the visibility of the target. (August 2020) - Cilia, Federica; Touchet, Claire; Vandromme, Luc; Driant, Barbara Le
Background and aims: Response to joint attention (RJA) and initiation of joint attention (IJA) are impaired in pre-schoolers with autism spectrum disorder (ASD). Children's response to joint attention may depend on the presence of the target in the child's field of vision or on the type of deictic index (head and eye orientation, pointing and verbalisations) used by the adult to initiate joint attention. Methods: This study deals with 50 ASD children aged from 2 years 8 months to 11 years 7 months, with a communicative level comparable to children under 31 months of age, according to the French version of the Early Social Communication Scales (ECSP, by its French acronym). We compared the aforementioned ASD children with 50 typically developing (TD) children, aged 9 to 30 months who had no communication disorders according to the ECSP. During the ECSP test, we analysed joint attention behaviours on three posters present or absent from the children's visual field. Results: We did not observe any difference in the number of IJAs between groups, but ASD children were less responsive than TD children were. Our results showed a developmental progression in the responses of children with ASD if several deictic cues were used by an adult simultaneously (looking and pointing, or looking and verbalising to indicate a target), whether the referent was present or absent from the child's visual field. In addition, we observed developmental progression when the referent was behind the child and the adult only used their gaze to refer to it. Conclusion: Thus, we argue that the type of cues used affects ASD children's response behaviours during joint attention towards a referent that may be present or absent from their visual field. Implications: Regarding the social and the sensory difficulties of children with ASD, many therapeutic approaches focus their intervention methods on non-verbal communication skills and joint attention. This fundamental research makes it possible to identify the most appropriate type of deictic index for children with ASD with developmental delay, depending on the presence or absence of the referent in the child's visual field.